Efektivitas Reformasi Birokrasi dalam Meningkatkan Pelayanan Publik - Mursalin Mursalin; Nurasia Natsir; Muhammad Anas (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Bureaucratic reform is the government's effort to improve the quality of public services in Indonesia. This study aims to analyze the impact of the implementation of the bureaucratic reform program on the quality of public services, evaluate obstacles and challenges in its implementation, and provide recommendations to strengthen the effectiveness of bureaucratic reform. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation studies. The results of the study show that the implementation of bureaucratic reform has had a positive impact on increasing the efficiency, effectiveness, and responsiveness of public services. There is an increase in public satisfaction with the quality of services provided. However, there are still several obstacles and challenges, such as resistance to change among bureaucrats, limited budgets and resources, and suboptimal coordination between government agencies. To strengthen the effectiveness of bureaucratic reform, it is necessary to strengthen leadership and leadership commitment, develop the capacity of bureaucratic human resources, increase transparency and accountability, and synchronize bureaucratic reform policies and programs. This research provides theoretical and practical implications for efforts to improve the quality of public services through bureaucratic reform in Indonesia.